Diet and lifestyle factors interact with MAPK genes to influence survival: The Breast Cancer Health Disparities Study - Slattery, Martha L. (2014)
INTRODUCTION: MAPK genes are activated by a variety of factors related to growth factors, hormones, and environmental stress. METHODS: We evaluated associations between 13 MAPK genes and survival among 1187 non-Hispanic white (NHW) and 1155 Hispanic/Native American women diagnosed with breast cancer. We assessed the influence of diet, lifestyle, and genetic ancestry on these associations. Percent Native American (NA) ancestry was determined from 104 Ancestry Informative Markers. Adaptive rank truncation product (ARTP) was used to determine gene and pathway significance. RESULTS: Associations were predominantly observed among women with lower NA ancestry. Specifically, the MAPK pathway was associated with all-cause mortality (P(ARTP)=0.02), but not with breast cancer-specific mortality (P(ARTP)=0.10). However, MAP2K1 and MAP3K9 were associated with both breast cancer-specific and all-cause mortality. MAPK12 (P(ARTP)=0.05) was only associated with breast cancer-specific mortality, and MAP3K1 (P(ARTP)=0.02) and MAPK1 (P(ARTP)=0.05) were only associated with all-cause mortality. Among women with higher NA ancestry, MAP3K2 was significantly associated with all-cause mortality (P(ARTP)=0.04). Several diet and lifestyle factors, including alcohol consumption, caloric intake, dietary folate, and cigarette smoking, significantly modified the associations with MAPK genes and all-cause mortality. CONCLUSIONS: Our study supports an association between MAPK genes and survival after diagnosis with breast cancer, especially among women with low NA ancestry. The interaction between genetic variation in the MAPK pathway with diet and lifestyle factors for all women supports the important role of these factors for breast cancer survivorship.